RSV epidemiology in Primary Care in four Italian regions: A prospective multi-center study in over 60-year-old adults across three winter seasons (2022 - 2023 - 2024) - Baglivo, Francesco; Tecchio, Federico; Sidoti, Maria; Pecchioli, Matilde; D’Atri, Antonella Lucia; Casini, Beatrice; Panatto, Donatella; Massaro, Elvira; Centrone, Francesca; Chironna, Maria; Pariani, Elena; Pellegrinelli, Laura; et al. (Annali di Igiene Medicina Preventiva e di Comunità, 2026)
Background: Respiratory syncytial virus (RSV) is an under-recognised cause of acute respiratory infections (ARIs) in older adults, despite a burden comparable to influenza and the recent availability of RSV vaccines. Robust community-based data from Italian primary care are lacking. Methods: We conducted a prospective, multicentre cohort study in four Italian regions (Liguria, Lombardy, Tuscany, Apulia) over three consecutive winter seasons (2022–2025). Community-dwelling adults ≥60 years presenting to participating general practitioners (GPs) with a WHO-defined ARI were enrolled. Nasopharyngeal swabs were collected and tested using a multiplex RT-PCR respiratory panel. RSV-positive participants were followed by telephone at day 14 (T14) and day 30 (T30). Adjusted prevalence ratios (PRs) for symptoms were estimated with Poisson regression. Results: Among 664 ARI episodes, 663 had a valid RSV result, and 88 were RSV-positive (13.3%). Positivity rates varied by season (21.7% in 2022–23, 11.9% in 2023–24, and 10.4% in 2024–25) and region (range: 11.2–28.3%), with peaks occurring between ISO weeks 51 and 10. The median age of RSV-positive patients was 75 years (IQR, 68–82); 42% were male. Compared with RSV-negative ARIs, RSV-positive cases had higher adjusted prevalence of cough (PR 1.07, 95% CI 1.02–1.13) and wheezing (PR 1.83, 95% CI 1.14–2.93); other symptoms overlapped substantially. RSV-B predominated (68.2%). Any co-infection occurred in 35.2% of RSV-positive cases, mainly with Haemophilus influenzae and Streptococcus pneumoniae. Median illness duration was 19.5 days (IQR 11.3–30.0). Within 14 days, 65.9% re-contacted their GP and 10.6% sought additional medical care; emergency visits (3.5%) and hospitalisations (2.4%) were uncommon. Conclusions: Across three winters, RSV accounted for approximately one in eight medically attended ARIs in Italian adults ≥60 years, with prolonged illness also leading to hospitalisations and frequent re-consultations. These findings provide baseline data to support adult RSV vaccination policies and integration of RSV into routine respiratory surveillance in Italy.